Natural Material Innovation. Earth and Halloysite Nanoclay for a sustainable challange - Cesare Sposito; Francesca Scalisi (Agathón)
Within the cultural debate that considers the environmental issue as a priority and with reference to the studies and researches that over the last years have supported compound materials containing rammed earth, the Authors, aware of the need of giving to the relationship of Project and Matter a key role, supported by the characteristics of Architectural Technology, show the results of an experimentation that aims to improve the performance of rammed earth with the contribution of nanotechnologies, developing a ‘new material’ with a reduced embodied energy and a reduced amount of CO2 emissions into the atmosphere.